Error Estimates for a New H^1-Galerkin EMFEM of PIDEs with Nonlinear Memory - et. al., Ali Kamil Al-Abadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, the error estimate of -Galerkin expanded mixed finite element methods (EMFEMs) is studied by investigating the semi discrete and fully discrete for parabolic integro-differential equations (PIDEs) with a nonlinear memory. We carried out theoretical survey for studying the existence and uniqueness of the numerical schemes.